Key challenges contributing to the survival of single mothers - Rahman, Noor Watee; Abdullah, Haslinda; Darus, Norazlina; Ali Mansor, Amiraa (TextRoad Publication, 2017)
Nowadays, the role of single mother is challenging especially when the single mothers are head of households and who are having children. In Malaysia, the challenges of single mother are related with the definition of single mother, children, financial, education, healthcare, legal assistance as well as registration with e-Kasih. The increase in the numbers of divorced women and widows has created a zone of illnesses after being a single mother and it became worse when their life are at greater risk of poverty. This study is using literature review for further discussion. Ultimately, this study will discuss about what are the factors to the issues and the impact on their life.